Learning Strategies at Muhammadiyah 5 Tulangan during the Covid 19 Pandemic - Nisful Laili Nurjanah; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
The research he did was to find out the strategies applied at SMP Muhammadiyah 5 Tulangan in learning during the covid 19 pandemic. This scientific work contains the history, strategies, challenges and facilities at SMP Muhammadiyah 5 Tulangan. This research is called descriptive qualitative research. The data collection technique of this research is through interviews, documentation, and observation. results of research at SMP Muhammadiyah 5 Learning reinforcement was boldly carried out during this covid 19 pandemic. Therefore, the covid 19 pandemic for education made the education system and curriculum change. The educational curriculum is shorter in learning during this pandemic, apart from negative impacts, there are also positive impacts, such as the emergence of unlimited creativity, collaboration between parents and teachers